2017
DOI: 10.1002/14651858.cd004305.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare financing systems for increasing the use of tobacco dependence treatment

Abstract: Full financial interventions directed at smokers when compared to no financial interventions increase the proportion of smokers who attempt to quit, use smoking cessation treatments, and succeed in quitting. There was no clear and consistent evidence of an effect on smoking cessation from financial incentives directed at healthcare providers. We are only moderately confident in the effect estimate because there was some risk of bias due to a lack of blinding in participants and researchers, and insufficient in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(50 citation statements)
references
References 99 publications
2
46
1
1
Order By: Relevance
“…Previous research has also found that covering the cost of smoking cessation therapy increases its use. 24 Finally, the interviewed employees appreciated the employers’ initiative to offer a smoking cessation training programme, because it was seen as an expression of caring for the employees’ health. Employees viewed the training programme as an opportunity and considered it an appropriate addition to the current company health plan.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also found that covering the cost of smoking cessation therapy increases its use. 24 Finally, the interviewed employees appreciated the employers’ initiative to offer a smoking cessation training programme, because it was seen as an expression of caring for the employees’ health. Employees viewed the training programme as an opportunity and considered it an appropriate addition to the current company health plan.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Full financial coverage of the costs of smoking cessation treatment had an effect size of 1.77 on abstinence when compared with no incentive in a healthcare setting. 12 We conservatively estimate an effect size of 1.25 for a small financial incentive to use smoking cessation services combined with CBR in a community-based trial. Validated abstinence at 6 months is therefore expected to be 11.0% in the intervention group and 5% in the control group.…”
Section: Methods and Analysismentioning
confidence: 99%
“… 11 12 Financial incentives increased service enrolment 13 and use of tobacco-dependent treatment (medications, nicotine replacement therapies and counselling) 14–17 and service providers have offered them effective treatments to increase abstinence. 12 Our previous trial revealed that time constraints and low interest are the main barriers to use smoking cessation services. 9 Although smoking cessation services in Hong Kong are mostly free or charge minimal fees, proactive models that offer referral assistance with a small financial incentive may increase smokers’ motivation to overcome perceived barriers.…”
Section: Introductionmentioning
confidence: 99%
“…89 The provision of prompts and reminders, 90 decision support tools embedded into medical software, 91 the establishment of referral services and pathways, 92,93 and systems of financial reimbursement of care were effective in improving the management of tobacco addiction by health services. 94,95 Such strategies are also likely to be required to support improvements in the delivery of health services to prevent and treat obesity. World Obesity, a federation of member organisations in more than 50 countries, offers e-learning platforms, internationally accredited certification in obesity management, and a range of resources to treat patients with obesity.…”
Section: Provider Capacity and Implementation Supportsmentioning
confidence: 99%